2021
DOI: 10.11591/ijere.v10i4.22028
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties in implementing 21st century skills competence in vocational education learning

Abstract: <span>The 21st century learning requires complex competencies, transformations of technology-based learning and non-cognitive skills need. This situation makes it difficult for teachers of Indonesian vocational education apply 21st century skills. This study aimed to analyze the level of difficulty of teachers and students in vocational education and analyzing the differences in the difficulties faced in vocational education. This research used survey research with a quantitative approach. A total of 178… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 27 publications
0
69
0
3
Order By: Relevance
“…While CPD addresses a rather general perspective and the frame where learning arrangements could take place, the construct of 21 st century skills offer a particular perspective about necessary skills for professional development (Hamby 1992;Mutohhari, et al 2021). DiBenedetto (2019) states that 21 st century skills are likely to be obtained via a mix of formal qualification, informal learning activities and a learning culture characterised by the presiding company or domain.…”
Section: St Century Skillsmentioning
confidence: 99%
“…While CPD addresses a rather general perspective and the frame where learning arrangements could take place, the construct of 21 st century skills offer a particular perspective about necessary skills for professional development (Hamby 1992;Mutohhari, et al 2021). DiBenedetto (2019) states that 21 st century skills are likely to be obtained via a mix of formal qualification, informal learning activities and a learning culture characterised by the presiding company or domain.…”
Section: St Century Skillsmentioning
confidence: 99%
“…TVET learning in the COVID-19 era must still be carried out and carried out through distance. The role of TVET is considered to be able to provide life skills even students can obtain competencies that are aligned in the industry [26], [27]. At present, online medium-based learning is a solution in a pandemic situation.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, several research reports and review reports agreed on the problem of unpreparedness for e-learning due to a lack of competence in using digital technology to use e-learning systems (Almaiah et al, 2020;Helm, Huber, & Loisinger, 2021;Pokhrel & Chhetri, 2021;Toquero, 2020). The unpreparedness of the students was identified through their low media information, lack of familiarity with learning management systems, lack of understanding of the supporting equipment needed, limited accessibility and a crisis of attitudes and ethics in the use of digital technology (Astuti et al, 2022;Mutohhari, Sutiman, Nurtanto, Kholifah, & Samsudin, 2021;Sutiman, Sofyan, Soenarto, Mutohhari, & Nurtanto, 2022). In line with this, other studies also identified students' lack of experience in using technology and supporting equipment to support e-learning, thus requiring competency development in that direction (Daniel, 2020).…”
Section: Technological Competencies and Motivation For E-learning Rea...mentioning
confidence: 99%